Community Empowerment and Sustainable Economic Development in Karang Tunggal Village, East Kalimantan - I Putu Gede Didik Widiarta; Dinar Anindyasari; Cori Qamara; Dede Aprylasari (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
Community service was conducted to socialize green marketing techniques to goat farmers. A total of 65 participants consisting of farmers and local officials actively took part in discussions, workshops, and group work with an interactive participatory approach to increase knowledge on sustainable marketing. The methodology used covered the needs of the farmers through field observations and discussions with the community. The results of these discussions showed a 75% increase in knowledge of green marketing concepts and identified competitive advantages in promoting the environmental benefits of their products. There was a change in perception as now was the time to attract environmentally conscious consumers. Therefore, it is important to advance the economic resilience of villages by providing sustainable marketing. Equipping farmers with sustainable marketing knowledge and instruments helps Karang Tunggal Village become an example for other villages in improving market competitiveness.